Characterisation of the role of Bruton's tyrosine kinase in toll-like receptor signalling - Doyle, Sarah (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2007)
Toll-like receptors (TLRs) are the primary surveillance system for the detection of pathogens and are crucial to the activation of the host innate response. TLRs contain an extracellular leucine rich repeat region which recognises foreign molecular patterns, and an intracellular Toll/IL-1R/Resistance (TIR) domain. B ruton’s tyrosine kinase (Btk) is a member of the Tec family of protein tyrosine kinases and has been shown to be a TIR interacting protein by binding to the TIR domains of TLR4, 6, 8 and 9 in a Yeast-two-hybrid assay. As the TIR domain has been shown to be critical for signal transduction from all TLRs, the aim of this study was to characterise the role for Btk in TLR signalling.
Keywords: Biochemistry, Ph.D.; Ph.D. Trinity College Dublin